A new species of Campsurus Eaton, 1868 (Ephemeroptera: Polymitarcyidae) from Brazil - Cabral, Jeniffer; Salles, Frederico F.; Mariano, Rodolfo (Zootaxa, 2022)
Campsurus is the most species-rich genus in Polymitarcyidae, and it is divided into four groups. A new species is described and illustrated here based on male imagos. Campsurus molinerii sp. nov. seems to be similar to C. nessimiani, C. dasilvai, and C. cuyuniensis because of the shape of penes and pedestal. The new species differs from them by the main penis lobe being expanded laterally and slightly curved ventrally, with the apex acute and curved ventrally outwards, the apical portion almost cylindrical with apex in ventral view pointed, secondary membranous lobe cylindrical and relatively long, and the outer projection of pedestal with apical condyle process-like projection.